8.2k views
5 votes
What is the solution to the equation by -2(y + 1) = 3(y – 2) + 6?

User Shaharmor
by
4.9k points

2 Answers

3 votes

Answer: y= -2.5

Explanation:

Distribute the -2 and 3 into the parentheses. -6 + 6 cancels out so you are left with 3y on the right side. Add 2y to the right side leaving you with -2=5y. Divide both sides by -2

User Hubidubi
by
4.6k points
1 vote

Answer:


\boxed{ \bold{ \boxed{ \sf{ </strong><strong>y</strong><strong> = - 0.4}}}}

Explanation:


\sf{ - 2(y + 1) = 3(y - 2) + 6}

Distribute -2 through the parentheses

Similarly, Distribute 3 through the parentheses


\sf{ - 2y - 2 = 3y - 6 + 6}

Since two opposites add up to zero , remove them


\sf{ - 2y - 2 = 3y}

Move 3y to Left hand side and change it's sign

Similarly, move -1 to right hand side and change it's sign


\sf{ - 2y - 3y = 2}

Collect like term


\sf{ - 5y = 2}

Divide both sides of the equation by -5


\sf{ ( - 5y)/( -5 ) = (2)/( - 5) }

Calculate


\sf{ - 0.4}

Hope I helped!

Best regards!

User Somethinghere
by
5.4k points